Jerome and the Monastic Clergy : a Commentary on Letter 52 to Nepotian, with Introduction, Text, and Translation. - Cain, Andrew (Vigiliae Christianae, Supplements., 2013)
In Jerome and the Monastic Clergy Andrew Cain provides the first full-scale commentary on Jerome's famous Letter to Nepotian along with an introduction, newly revised Latin text, and English translation.